Formulasi Tepung Ikan Gabus (Channa Striata), Tepung Kecambah Kedelai (Glycine Max Merr)Tepung Kecambah Jagung (Zea Mays) Untuk Balita Gizi Kurang - Sholihah, Rofiatu; Santoso, Agus Heri; Suwita, I Komang (Jurnal Informasi Kesehatan Indonesia (JIKI), 2017)
Abstract: The purpose of this study was to determine the effect of the formulation of Cork FishFlour(Channa Striata), Soybean Sprouts Flour (Glycine Max Merr) Corn Sprouts Flour(Zea Mays) toValue Energy, Quality Chemicals, Quality Protein, and Quality Appearance Cereal Instant for MalnutritionToddlers. This research is an experimental laboratory with experimental design completelyrandomized design (CRD) using a 4 stage treatment that the proportion of Cork Fish Flourflour sproutsoybean flour sprouts of corn is 10: 12: 78 (P1), 8: 18: 75 (P2) , 5: 22: 73 (P3), 4: 15: 81 (P4). The resultsshowed that the proportion of a significant effect on moisture, ash, protein, fat, carbohydrates, energyvalue, and a sense of instant cereal, but not significant effect on color, aroma, and texture.